Orthodontic Management of Class II Malocclusion with Clear Aligners: Mandibular Advancement vs. Class II Elastics - Elisabetta Cretella Lombardo; Letizia Lugli; Roberta Lione; Patrizio Bollero; Paola Cozza; Chiara Pavoni (Children)
Background: This cephalometric study aimed to evaluate the effects of clear aligner therapy in growing individuals with Class II malocclusion, comparing two functional approaches: the use of Class II elastics or the Mandibular Advancement (MA). Methods: Cephalometric data from 39 patients with Class II malocclusion treated using clear aligners either combined with Class II elastics (EL group; n = 18) or Mandibular Advancement (MA group; n = 21) were analyzed and compared with an untreated control group (UC2; n = 15). Results: Both treatment groups (EL and MA) showed a significant reduction in the ANB angle compared to the control (MA: −1.5°; EL: −2.2°; UC2: +0.2°). An increase in mandibular length, as measured by Co–Gn, was observed in both the EL and MA groups (+5.5 mm and +8.3 mm, respectively) relative to the control group. Soft tissue analysis of the Pg–TVL distance from T1 to T2 revealed the most substantial forward displacement of the chin in the MA group (MA: +2.0 ± 3.7 mm; EL: +0.5 ± 0.7 mm; UC2: −1.6 ± 3.3 mm). Vertically, the MA group exhibited a more marked decrease in the palatal-mandibular plane angle than the other groups. Both treatment modalities significantly reduced overjet and overbite from T1 to T2. Conclusions: The EL and MA appliances effectively advanced the mandible, leading to significant improvements in the sagittal relationship, overjet, and overbite while maintaining stable vertical control. Additionally, the MA group exhibited a more pronounced forward movement of the soft tissue chin.